2018
DOI: 10.1128/jcm.01990-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Clostridium difficile Sequence Type 37 Genotype by Matrix-Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry

Abstract: multilocus sequence type 37 (ST37), which mainly corresponds to ribotype 017, has been a dominant genotype circulating in China. In this study, we report the use of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) to analyze and characterize 204 clinical isolates, including 49 ST37 and 155 non-ST37 isolates collected in China and other countries. The distributions of two major protein peaks ( 3,242 and 3,286) were significantly different between ST37 and non-ST37 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…In addition, according to Cooper et al [26], the animal call rate was also related to genotyping accuracy, the individual call rate ranged from 96-99% in our study. All the above results demonstrated that the genotyping data got in the present study was validated, and the method of MALDI-TOF MS could be a stable platform for genotyping those SNPs [27,28].…”
Section: Resultssupporting
confidence: 63%
“…In addition, according to Cooper et al [26], the animal call rate was also related to genotyping accuracy, the individual call rate ranged from 96-99% in our study. All the above results demonstrated that the genotyping data got in the present study was validated, and the method of MALDI-TOF MS could be a stable platform for genotyping those SNPs [27,28].…”
Section: Resultssupporting
confidence: 63%
“…In addition, according to Cooper et al [21], the call rate of the animal was also related to genotyping accuracy, the individual call rate ranged from 96-99% in our study. All the above results revealed that the genotyping data got in the present study was validated, and the method of MALDI-TOF MS could be a stable platform for genotyping those SNPs [22,23].…”
Section: Discussionsupporting
confidence: 61%
“…A recent study in China reported that RT 017 can also be identified using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) with high sensitivity and specificity [45]. However, this study did not include other C. difficile strains from clade 4 and another Chinese study suggested that different clade 4 strains may not be distinguishable by this method [46].…”
Section: Characteristics Of C Difficile Rt 017mentioning
confidence: 99%